The Effect of Fun Learning Methods in Increasing Students' Learning Motivation - Jibril Olaniyi Ayuba (Yayasan Avicenna, 2023)
This study aims to analyze the effect of fun learning methods on improving learning motivation of senior high school students in Islamic Studies subjects in Ilorin, Nigeria. This study uses a quantitative approach with a survey design, and involves 30 students as samples taken through purposive sampling techniques. The research instrument is a questionnaire with a Likert scale, while data analysis is carried out using the Pearson correlation test and the coefficient of determination (R²) with the help of SPSS software version 16.0. The results of the study indicate that there is a positive and significant relationship between the application of the fun learning method and student learning motivation, with a correlation coefficient value of 0.642, which exceeds the critical value at the 5% and 1% significance levels. The coefficient of determination value of 0.412 indicates that 41.20% of the variation in learning motivation can be explained by the application of the fun learning method, while the rest is influenced by other factors. The implications of these findings indicate that the application of fun learning strategies can substantially increase student engagement and persistence in the learning process. Therefore, teachers are advised to design conducive and interactive learning in order to foster students' intrinsic motivation. This research contributes to pedagogical practice by emphasizing the importance of a positive and enjoyable learning atmosphere in supporting educational success.